Comprensión lectora y el desarrollo del razonamiento lógico de los estudiantes del sexto año de la Escuela de Educacion Basica de la Unidad Educativa Juan E. Verdesoto del cantón Babahoyo, provincia de los Ríos. - Valencia Ganchozo, Jerry Paul (2018)
There are many activities that must be addressed during the development of the teaching-learning process, especially when the goal is directed to logical thinking, facts that undoubtedly puts many teachers in a bad position, one of the alternatives being the use of comprehension. reader as a dynamic tool that helps to improve the operations and mental processes of students in the stage of basic education. In this research work is intended to show the influence of reading comprehension and the development of logical reasoning of sixth-year students of the School of Basic Education of the Educational Unit Juan E. Verdesoto Babahoyo canton, province of Los Ríos year 2017, for which it is necessary to determine the methodology, starting with the type of exploratory, descriptive and explanatory research applied in a systematic manner according to the needs, the inductive and deductive methods, the techniques for gathering information starting with observation, then with interviews and surveys, whose instrument was the semi-structured questionnaire, open and closed, formally and informally. On the other hand, it is concluded that there are few teachers that include activities aimed at the incorporation of reading comprehension within school activities and with this the development of students' logical thinking is limited, which makes it difficult to apply and obtain positive results, for this reason the proposal of elaboration of a workshop program of didactic strategies aimed at improving reading comprehension and guaranteeing the development of the logical thinking of the students of the sixth year of the basic education school of the Educational Unit Juan E is presented Verdesoto from the Babahoyo canton, province of Los Ríos.